2015
DOI: 10.1186/s12906-015-0525-7
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of anti-inflammatory activity of standardised Andrographis paniculata extracts and pure andrographolide

Abstract: BackgroundThe anti-inflammatory activity of Andrographis paniculata (Acanthaceae), a traditional medicine widely used in Asia, is commonly attributed to andrographolide, its main secondary metabolite. Commercial A. paniculata extracts are standardised to andrographolide content. We undertook the present study to investigate 1) how selective enrichment of andrographolide in commercial A. paniculata extracts affects the variability of non-standardised phytochemical components and 2) if variability in the non-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 74 publications
3
31
0
Order By: Relevance
“…Besides, APN could significantly lower the levels of these cytokines and chemokines in a dose-dependent manner, suggesting a potent anti-inflammatory effect of APN for PID. As andrographolide is the major bioactive substance and has a critical effect on inhibiting the release of an important proinflammatory factor TNF-α in APN [43], it may also contribute importantly to suppressing the inflammatory response in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, APN could significantly lower the levels of these cytokines and chemokines in a dose-dependent manner, suggesting a potent anti-inflammatory effect of APN for PID. As andrographolide is the major bioactive substance and has a critical effect on inhibiting the release of an important proinflammatory factor TNF-α in APN [43], it may also contribute importantly to suppressing the inflammatory response in this study.…”
Section: Discussionmentioning
confidence: 99%
“…They are also the very first ones revealing cognitive function improving potentials of andrographolide and of the A. paniculata extract studied. Although this medicinally used extract (KalmCold Õ , or AP) is highly enriched in andrographolide (32.2%, w/w), apart from such labdane terpenes this and other andrographolide enriched extracts of the plant also contain numerous other bioactive phytochemical with andrographolide like anti-inflammatory and other bioactivities (Chandrasekaran et al 2011;Low et al 2015). However, the observed efficacies of AP and pure andrographolide in counteracting cognitive deficits and all biochemical abnormalities in the brain quantified in this study were always qualitatively as well as quantitatively almost equal.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographis paniculata (Acanthaceae) is known as sambiloto (Indonesia), kalmegh (India) and chuanxinlian (China), which is used as an herbal medicine in Asia [7]. Based on previous studies andrographolide has been shown to have pharmacological effects as anti-inflammatory through its influence on cytokines that play a role in the inflammatory process [7][8][9][10][11]. With the discovery of anti-inflammatory role of andrographolide, its potential effect in inflammation has gradually attracted much attention, especially in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%